2010
DOI: 10.1007/s10549-010-1187-2
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant dose-dense doxorubicin plus cyclophosphamide followed by dose-dense nab-paclitaxel is safe in women with early-stage breast cancer: a pilot study

Abstract: Every-2-week (dose-dense) adjuvant doxorubicin (A) plus cyclophosphamide (C) followed by paclitaxel is a safe and effective adjuvant chemotherapy regimen. Every-3-week nab-paclitaxel is safe and more effective at 50% higher dose than every-3-week paclitaxel in metastatic breast cancer (BC). This study evaluated the safety of adjuvant dose-dense AC followed by dose-dense nab-paclitaxel for early-stage BC. Women with operable, histologically confirmed BC received four cycles of dose-dense A 60 mg/m(2) plus C 600… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 12 publications
1
21
0
Order By: Relevance
“…In addition, the administration of nab-paclitaxel every second week may offer an efficacy advantage over administration every third week (29). Previous studies demonstrated the safety of substituting nab-paclitaxel for conventional paclitaxel in the dose-dense adjuvant regimen (30, 31). To inform subsequent and ongoing clinical trials, we built on these observations by testing the cardiac safety and tolerability of bevacizumab added to adjuvant dose-dense doxorubicin–cyclophosphamide followed by nab-paclitaxel and incorporated studies of potential predictors of HTN and CHF.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the administration of nab-paclitaxel every second week may offer an efficacy advantage over administration every third week (29). Previous studies demonstrated the safety of substituting nab-paclitaxel for conventional paclitaxel in the dose-dense adjuvant regimen (30, 31). To inform subsequent and ongoing clinical trials, we built on these observations by testing the cardiac safety and tolerability of bevacizumab added to adjuvant dose-dense doxorubicin–cyclophosphamide followed by nab-paclitaxel and incorporated studies of potential predictors of HTN and CHF.…”
Section: Introductionmentioning
confidence: 99%
“…26 Women with high risk breast cancer (T 1-3 N 1-2 , or T 2 N 0 disease) were enrolled to receive four cycles of dose-dense A (60 mg/m 2 ) plus C (600 mg/m 2 ) with peg-filgrastim, followed by dose-dense nab-paclitaxel (260 mg/m 2 ) with peg-filgrastim given as needed. 30 patients received four cycles of dose-dense AC and 29 women proceeded to nab-paclitaxel therapy.…”
Section: Phase II Studiesmentioning
confidence: 99%
“…137 To this end, the combination of adjuvant dosedense doxorubicin plus cyclophosphamide followed by dosedense nab-paclitaxel was recently found to be safe for use in women with early-stage breast cancer. 138 Interestingly, it has also been suggested that SPARC may be a stromal tumor suppressor protein which conveys resistance to therapies. In fact, a recent work demonstrated that a peptide analogous to SPARC has tumor-regressing and chemo-sensitizing activities in vitro and in pre-clinical animal models.…”
Section: Therapeutic Interventionsmentioning
confidence: 99%
“…Breast cancer models and clinical trials 131,132,137,138 Prostate cancer clinical trial 133 Pancreatic cancer clinical trial 134 Note that additional (not listed) reagents may be available. The relevant targets, therapeutic agents and models used are provided.…”
mentioning
confidence: 99%